2015
DOI: 10.1371/journal.pone.0119166
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Edaphic Environment and Climate in Structuring Phylogenetic Pattern in Seasonally Dry Tropical Plant Communities

Abstract: Seasonally dry tropical plant formations (SDTF) are likely to exhibit phylogenetic clustering owing to niche conservatism driven by a strong environmental filter (water stress), but heterogeneous edaphic environments and life histories may result in heterogeneity in degree of phylogenetic clustering. We investigated phylogenetic patterns across ecological gradients related to water availability (edaphic environment and climate) in the Caatinga, a SDTF in Brazil. Caatinga is characterized by semiarid climate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 45 publications
4
60
0
4
Order By: Relevance
“…Positive LifeFormNRI values show that there is a tendency of related species to resemble each other more than species drawn at random from the phylogeny, indicating that close relatives share more functional traits and show higher niche overlap than expected by chance. Similar patterns from other savannalike formations have been detected by previous studies (i.e., Qian & Zhang 2014;Moro et al 2015;Kuhlmann & Ribeiro 2016). …”
Section: Discussionsupporting
confidence: 90%
“…Positive LifeFormNRI values show that there is a tendency of related species to resemble each other more than species drawn at random from the phylogeny, indicating that close relatives share more functional traits and show higher niche overlap than expected by chance. Similar patterns from other savannalike formations have been detected by previous studies (i.e., Qian & Zhang 2014;Moro et al 2015;Kuhlmann & Ribeiro 2016). …”
Section: Discussionsupporting
confidence: 90%
“…By contrast, Abreu et al (2012), who investigated typical and stony cerrado in Goiás State, Brazil, found a clear relationship between the soil and plant species composition, and a much less pronounced link with geographic distance. We believe that, in situations where edaphic properties are more homogeneous, such as the present study, space is the determining factor, whereas in environments with highly distinct substrates (Abreu et al, 2012;Mews et al, 2016;Moro et al, 2015) the properties of the soil determine the distinct structure and species composition of the different Cerrado phytophysiognomies.…”
Section: Discussionmentioning
confidence: 69%
“…Legendre et al, 2002;Peres-Neto and Legendre, 2010;Moro et al, 2015;Neves et al, 2015;Mews et al, 2016), although Mews et al (2016) used an approach of this type. This new approach may help improve the understanding of the factors and mechanisms that mold the distribution of the flora and the structure of the vegetation of the Cerrado.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this precipitation is heterogeneously distributed as a result of two large moisture gradients, one in the north-south direction determined by decreasing precipitation, and the other in the east-west direction due to the eff ect of increasing continentality (Rodal et al 2008). Th e most common soil of the region is of crystalline origin, but areas of sedimentary soil are also present (Moro et al 2015;Moro et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Th e Caatinga domain (seasonally dry tropical forest), with features that distinguish it from the other main biomes of the world, exhibits marked variation in its response to environmental heterogeneity, which is related to the interaction among edaphic, climatic and historical factors (Moro et al 2015). Th e hyperxerophytic vegetation of the Caatinga grows in crystalline soil and is predominant in this phytogeographical region (Moro et al 2016).…”
Section: Introductionmentioning
confidence: 99%